2015
DOI: 10.1021/es5055012
|View full text |Cite
|
Sign up to set email alerts
|

Regional Ozone Impacts of Increased Natural Gas Use in the Texas Power Sector and Development in the Eagle Ford Shale

Abstract: The combined emissions and air quality impacts of electricity generation in the Texas grid and natural gas production in the Eagle Ford shale were estimated at various natural gas price points for the power sector. The increased use of natural gas in the power sector, in place of coal-fired power generation, drove reductions in average daily maximum 8 h ozone concentration of 0.6-1.3 ppb in northeastern Texas for a high ozone episode used in air quality planning. The associated increase in Eagle Ford upstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 10 publications
1
33
0
Order By: Relevance
“…This area includes portions of several counties in the EFS -notably Atascosa, Bee, Karnes, Live Oak, and Wilson counties -which are members of AACOG (2015). Pacsi et al (2015) found that, among all counties in the EFS, NO x emissions from these counties had the greatest impact on ozone enhancement in Bexar County, home to the city of San Antonio. Therefore, quantifying emissions from these counties in the core of the EFS is a particularly important step in assessing the air quality impacts of oil and gas operations in the San Antonio area.…”
Section: Partitioning Of Alkane Sourcesmentioning
confidence: 96%
See 1 more Smart Citation
“…This area includes portions of several counties in the EFS -notably Atascosa, Bee, Karnes, Live Oak, and Wilson counties -which are members of AACOG (2015). Pacsi et al (2015) found that, among all counties in the EFS, NO x emissions from these counties had the greatest impact on ozone enhancement in Bexar County, home to the city of San Antonio. Therefore, quantifying emissions from these counties in the core of the EFS is a particularly important step in assessing the air quality impacts of oil and gas operations in the San Antonio area.…”
Section: Partitioning Of Alkane Sourcesmentioning
confidence: 96%
“…Bexar County ozone design values for recent years exceeded both the current and previous ozone standards of 70 and 75 ppb (Alamo Area Council of Governments (AACOG), 2014; US Environmental Protection Agency, 2015b), while ozone levels in Houston, a nonattainment area, have dropped below levels in San Antonio. Modeling studies for the San Antonio region (AACOG, 2013a;Pacsi et al, 2015) have found that emissions from the EFS contribute significantly to regional ozone formation. However, these studies have utilized emission inventories that may underestimate the magnitude of emissions from oil and gas operations in the shale area.…”
Section: Introductionmentioning
confidence: 99%
“…The Burgos Basin represents around two-thirds of the estimated 550 trillion cubic feet of shale gas recoverable in Mexico, which is the sixth largest reservoir in the world [50]. The introduction of shale gas extraction and energy production will likely increase the regional emissions of VOCs and NO x , impacting the photochemistry of the MMA airshed during events of enhanced regional transport [51]. Increasing NO x levels upwind of the MMA could foster higher O 3 levels.…”
Section: Box Modelingmentioning
confidence: 99%
“…Numerous studies have also shown that regional ozone (O 3 ), a health hazard and criteria pollutant regulated by the U.S. Environmental Protection Agency, is also influenced by O&NG emissions during both summer (e.g. Kemball-Cook et al, 2010;McDuffie et al, 2016;Pacsi et al, 2015;Rodriguez et al, 2009) and winter seasons (e.g. Ahmadov et al, 2015;Carter and Seinfeld, 2012;Edwards et al, 2013Edwards et al, , 2014Field et al, 2014;Helmig et al, 2014;Oltmans et al, 2013;Schnell et al, 2009).…”
Section: Introductionmentioning
confidence: 99%